PERBEDAAN MOTIVASI KERJA ANTARA ORANG BALI YANG BEKERJA DI BALI DENGAN ORANG BALI YANG MERANTAU DI SULAWESI TENGAH - Putra, A.A Ngr. Agung Adi Pratama Wicaksana; Indrawati, Komang Rahayu (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
This research aims to find out wheter there is a difference between the work motivation of Balinese whose are working in Bali with Balinese whose migrated in Central Sulawesi. The research method used was quantitative research approach using comparative study. Primary data obtained from questionnaire drawn up based on work motivation theory of McClelland. Independent variables in this study are the Balinese whose work in Bali and The Balinese whose migrated to Central Sulawesi. The dependent variable is the work motivation. The sampling method used was cluster random sampling. The subject of this research is 90 Balinese whose working in Bali that domiciled in Banjar Benet, Mengwi and 90 Balinese who migrated to Central Sulawesi, who domiciled in South Palu. The criteria of the sample are at least 30 years old, at least have worked for 5 years, and for the Balinese that migrated to Central Sulawesi at least already migrated for 5 years. Research analysis using comparison test with independent sample t-test in SPSS 17. Result of the data analysis showed that the value P from comparison test is 0.009 so P<0.05, which mean there is difference between the work motivation of Balinese whose working in Bali and Balinese who migrated in Central Sulawesi. Other than that obtained from t value, revealed that the work motivation of Balinese who migrated to Central Sulawesi is higher than the Balinese whose work in Bali. Keywords: Work Motivation, Balinese, Migrant, MClelland, Comparative studies